UNDERSTANDING SYLLABLES: THEIR FORMATION AND DIVISION (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article delves into the core concept of a syllable, offering a comprehensive exploration of its formation and separation. It provides a clear definition of a syllable as a fundamental sound unit in language and highlights its essential components: the onset, nucleus, and coda. The article categorizes syllables into various types, such as open, closed, stressed, and unstressed, and explains their structural differences.